Takhrij and Syarah Hadith of Agrotechnology Agriculture in Life - Mona Miranda; Wahyudin Darmalaksana; Salamet Ginandjar (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith with regard to agrotechnology. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The results and discussion of this research show that the miracle that cannot be forgotten in life, about how humans can live and the foundation of humans can survive is because of food and agriculture. The conclusion of this agriculture is that everyone can farm regardless of the background of the people because agriculture is important for life. This study recommends a policy consideration.